Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
[tex]\frac{\sqrt{5}*125^\frac{2}{3} *(\frac{1}{5} )^{-2}}{25^{-\frac{1}{2} }} =\frac{5^\frac{1}{2}*(5^3)^\frac{2}{3}*5^2 }{(5^2)^{-\frac{1}{2} }} =\frac{5^{\frac{1}{2} +3*\frac{2}{3}+2} }{5^{2*(-\frac{1}{2} )}} =\frac{5^{4\frac{1}{2} }}{5^{-1}} =5^{4\frac{1}{2}-(-1) }=5^{5\frac{1}{2} }[/tex]
[tex]\dfrac{\sqrt{5}\cdot125^{\frac{2}{3}}\cdot(\frac{1}{5})^{-2}}{25^{-\frac{1}{2}}}=\dfrac{5^{\frac{1}{2}}\cdot(5^3)^{\frac{2}{3}}\cdot5^2}{(5^2)^{-\frac{1}{2}}}=\dfrac{5^{\frac{1}{2}}\cdot5^2\cdot5^2}{5^{-1}}=\dfrac{5^{\frac{1}{2}+2+2}}{5^{-1}}=\dfrac{5^{4\frac{1}{2}}}{5^{-1}}=5^{4\frac{1}{2}-(-1)}=\\\\=5^{4\frac{1}{2}+1}=5^{5\frac{1}{2}}=5^{\frac{11}{2}}[/tex]
Wykorzystano własności potęg i własności pierwiastków
[tex]\sqrt[n]{a^m}=a^{\frac{m}{n}}\\\\(a^m)^n=a^{m\cdot n}\\\\a^m\cdot a^n=a^{m+n}\\\\\frac{a^m}{a^n}=a^{m-n}[/tex]